Kriteria Penginapan Dalam Perkhidmatan Hospitaliti Mesra Muslim (phmm) Bagi Sektor Pelancongan Di Malaysia - Hisham Sabri; Latifah Mustafa; Khairil Faizal Khairi; Mohamad Yazis Ali Basah; Junaidah Abu Seman; Nazratul Aina Mohamad Anwar (Usuli Faqih Research Centre PLT, 2024)
The significant impact of tourism industry has made it one of dominant economic and social activities in Malaysia, which contribute to the increasing number of domestic and international tourists especially among the Muslim community. Thus, it is important for the industry to create the concept of Muslim Friendly Hospitality Services (MFHS) to cater this trend as an innovation in the tourism and hospitality sector in Malaysia. With the aim to explain the accommodation parameters in MFHS for the tourism sector based on the standard MS 2610:2015, this study uses the method of literature and text study. Furthermore, analysis of relevant documents, books and journals, articles, past studies are also referred to discuss the implementation framework of MS 2610: 2015 beside conducting interviews with experts in the industry related to the development of standard MS2610: 2015 to achieve the objectives of the study. Findings of this study found that there are still hospitality services that need to be strengthened to meet the MS 2610:2015 standard. Thus, this study has contributed by identifying the parameters of standardization in the implementation of MFHS in the tourism industry in Malaysia. Moreover, this study also clarified the concept of MFHS and the criteria measured for the tourism hospitality sector in Malaysia, which is expected to increase the credibility of an organization by applying noble values in management as well as driving the growth of Malaysia's halal tourism hub globally.